Between Rules and Freedom : A Legal Perspective on Unregistered Marriages for Civil Servants - Muhammad Arief Tungkagi; Nur Mohamad Kasim; Weny Almoravid Dungga (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to analyze the role of legislation in addressing cases of unregistered marriages conducted by Civil Servants (PNS). Utilizing a normative legal research method with a statute approach, this study employs library research, expert opinions, and an examination of Government Regulation No. 10 of 1983 in conjunction with Government Regulation No. 45 of 1990 concerning Marriage and Divorce Licenses for Civil Servants. These regulations have a hierarchy that refers to Law No. 16 of 2019 concerning amendments to Law No. 1 of 1974 on marriage. The perspective of this research is to evaluate the extent to which government regulations can control the functions and positions of civil servants as state apparatus faced with freedom of perspective, both from administrative, legal norms, and religious values.